Spatial Determinants of Recurrent Landslides Revealed Through Multi-Source GIS–Remote Sensing Integration in Kindo Didaye, Wolaita Zone, Ethiopia - Dabara, Deneke Dana (Geosfera Indonesia, 2025)
Landscape failure and associated landslide occurrence is one of common problem in many parts of the world in hilly and mountain areas. Study in such areas could enhance proper land use management practices. The objective of this study was to assess root causes of landslides occurrence with the use of Remote Sensing (RS) and GIS. In this study analytical hierarchy process (AHP), Spatial Multi-criteria evaluation (SMCE), and weighted linear combination (WLC) were used to produce landscape and landslide susceptibility map. In order to identify major causes of landscape failures and associated landslide problem field observation, Focus Group Discussion, and Key Informant Interview methods were employed. Geology (0.32), Slope steepness (0.24), soil texture (0.19), aspect (0.08) and drainage density (0.05) were found major causes for landslide susceptibility. Five susceptibility zones were identified in the study area. From the total area(308.44km2): very high susceptibility (28.75%), high susceptibility (22.46%), moderate susceptibility (20.97%), low susceptibility (8.01%), and very low susceptibility (19.81%). This shows that about 70.21% of the region in the south and east are prone to moderate to very high levels of landslide susceptibility. Information obtained from FGD and KII revealed that major causes of landslide occurrences besides to physical problems were landscape failures due to removal of indigenous plants around farmland boundaries, stream courses, hill sides and absence of modern landscape based soil and water conservation practices. Therefore, intervention with integrated indigenous and modern farmland management as well as income diversification for the farming communities is highly recommended.